Physiological Aspect Of Prasav(delivery) W.S.R. To Parturition - Kumar, Hemant; Sharma, Rajesh Kumar; Sharma, Dinesh Chandra (International Research Journal of Ayurveda & Yoga, 2021)
Parturition or labor is a physiological event involving a subsequential, integrated set of changes within the myometrium, decidua, and uterine cervix that occur gradually over a period of days to weeks. To proceed uterine contraction & dilatation of cervix, cervix shows biochemical connective tissue changes, and all these occurs usually before fetal membrane’s rupture. So it can be said that the process of confinement or delivery of fully matured fetus, on completion of normal pregnancy period is called parturition. Ancient ayurvedic texts given detail of every step of process of birth, with month wise growth description and parturition. In ayurvedic context (in shaarir sthan, acharya charak and sushrut both) explained about the period of delivery (prasav kaal), process of delivery, various symptoms just prior to delivery (prajayani), different stages of labor, concept of involuntary (aavi) and voluntary (pravahan) contractions. Ancient acharyas also explained different methods to induce smooth labor and resolve complication like obstructing labor (garbhasangha). In this review article Different physiological aspects of parturition are explained according to ayurvedic and modern context.